Case report: Significant liver atrophy due to giant cystic pheochromocytoma - Feng, Qingbo; Li, Hancong; Qiu, Guoteng; Cai, Zhaolun; Li, Jiaxin; Zeng, Yong; Huang, Jiwei (Frontiers in Oncology, 2022)
Introduction: Pheochromocytoma is a neuroendocrine tumor originating from chromaffin cells in the adrenal medulla. Giant pheochromocytomas with a maximum diameter of over 20cm are particularly rare. Case Presentation: We present a case of giant cystic pheochromocytoma in a 64 years old woman who found a right abdominal mass occasionally during the ultrasound examination, which is the largest pheochromocytoma ever documented in China. Our literature review identified 20 cases that diameter of over 20cm. The average age at diagnosis was 51.7 (range17–85) and 35% of cases didn't exhibit classic symptoms. Conclusion: Giant pheochromocytoma is an uncommon neoplasm. It can be discovered late due to a lack of clinical manifestations. Diagnosis is dependent on imaging recognition together with catecholamine secretion. Surgical resection is the only curative treatment for such tumors.